An Experimental Study of Microneedle‐Assisted Microparticle Delivery. Issue 10 (26th July 2013) - Zhang, Dongwei; Das, Diganta B.; Rielly, Chris D.
<x xml:space="preserve">Abstract</x> A set of well‐defined experiments has been carried out to explore whether microneedles (MNs) can enhance the penetration depths of microparticles moving at high velocity such as those expected in gene guns for delivery of gene‐loaded microparticles into target tissues. These experiments are based on applying solid MNs that are used to reduce the effect of mechanical barrier function of the target so as to allow delivery of microparticles at less imposed pressure as compared with most typical gene guns. Further, a low‐cost material, namely, biomedical‐grade stainless steel microparticle with size ranging between 1 and 20 μm, has been used in this study. The microparticles are compressed and bound in the form of a cylindrical pellet and mounted on a ground slide, which are then accelerated together by compressed air through a barrel. When the ground slide reaches the end of the barrel, the pellet is separated from the ground slide and is broken down into particle form by a mesh that is placed at the end of the barrel. Subsequently, these particles penetrate into the target. This paper investigates the implications of velocity of the pellet along with various other important factors that affect the particle delivery into the target. Our results suggest that the particle passage increases with an increase in pressure, mesh pore size, and decreases with increase in polyvinylpyrrolidone concentration. Most importantly, it is shown that MNs increase the penetration depths of the particles. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3632–3644, 2013